2021
DOI: 10.4236/jbm.2021.91001
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Factors of Developmental Attention Deficit Hyperactivity Disorder in Children

Abstract: Background: Attention deficit hyperactivity disorder is a common pediatric neurobehavioral disorder often treated in the primary care setting. It shows a high and chronic level of inattention, impulsivity/hyperactivity and/or both, and can affect more than 2 million school-age children. The researchers are not sure about the exact causes of the disorder, but it seems that apart from genetic factors, perinatal factors seem to dynamically contribute to the development of the disorder. Purpose: The aim of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…Studies in first-degree relatives with ADHD have shown 2 to 8 times higher risk for ADHD to be manifested in other family members ( 13 ). Therefore, girls with a history of perinatal disorders must be closely monitored for ADHD symptoms ( 14 ). Other factors that can contribute to insufficient ADHD diagnosis and non-referral for treatment of ADHD girls are the presence of comorbid psychiatric disorders (depression /anxiety) ( 15 , 16 ) which are responsible for the internalization of the symptoms, the presence of a comorbid compulsive-compulsive disorder, which is often accompanied by a perfectionist behaviour ( 17 ) and the lack of aggressiveness which is more obvious in boys than in girls ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in first-degree relatives with ADHD have shown 2 to 8 times higher risk for ADHD to be manifested in other family members ( 13 ). Therefore, girls with a history of perinatal disorders must be closely monitored for ADHD symptoms ( 14 ). Other factors that can contribute to insufficient ADHD diagnosis and non-referral for treatment of ADHD girls are the presence of comorbid psychiatric disorders (depression /anxiety) ( 15 , 16 ) which are responsible for the internalization of the symptoms, the presence of a comorbid compulsive-compulsive disorder, which is often accompanied by a perfectionist behaviour ( 17 ) and the lack of aggressiveness which is more obvious in boys than in girls ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Діти народжені з малою вагою, передчасно та із коротшим гестаційним віком асоціюються з підвищеним ризиком розвитку РАС, порівняно із тими, що мають велику вагу при народженні, народжуються пізно та із довшим гестаційним віком [62]. Неонатальна гіпоксія, яка виникає, наприклад, при дистресі плода чи обвитті пуповиною, може бути причиною розвитку РАС [63]. Перинатальна жовтяниця може з'явитися в результаті розпаду еритроцитів плода, що призводить до вивільнення білірубіну.…”
unclassified